Theory and applications of satisfiability testing -- SAT 2016 : 19th International Conference, Bordeaux, France, July 5-8, 2016, Proceedings /: 19th International Conference, Bordeaux, France, July 5-8, 2016, Proceedings. (2016) - Unknown
No abstract available